2003
DOI: 10.1126/science.1083970
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Spinal NMDA Receptor Currents by Spillover of Synaptically Released Glycine

Abstract: In the mammalian CNS, N-methyl-D-aspartate (NMDA) receptors serve prominent roles in many physiological and pathophysiological processes including pain transmission. For full activation, NMDA receptors require the binding of glycine. It is not known whether the brain uses changes in extracellular glycine to modulate synaptic NMDA responses. Here, we show that synaptically released glycine facilitates NMDA receptor currents in the superficial dorsal horn, an area critically involved in pain processing. During h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
3
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 24 publications
3
97
3
4
Order By: Relevance
“…D. Burrell, unpublished observations), possibly because application of sufficient amounts of glycine alone can induce LTP (Musleh et al, 1997;Lu et al, 2001;Man et al, 2003). This requirement for phasic application of glycine suggests that its extracellular concentration is regulated in the leech brain as occurs in the vertebrate CNS (Schell et al, 1995;Supplisson and Bergman, 1997;Ahmadi et al, 2003;Yang et al, 2003), but that some element of the experimental protocol disrupted this process.…”
Section: Discussionmentioning
confidence: 99%
“…D. Burrell, unpublished observations), possibly because application of sufficient amounts of glycine alone can induce LTP (Musleh et al, 1997;Lu et al, 2001;Man et al, 2003). This requirement for phasic application of glycine suggests that its extracellular concentration is regulated in the leech brain as occurs in the vertebrate CNS (Schell et al, 1995;Supplisson and Bergman, 1997;Ahmadi et al, 2003;Yang et al, 2003), but that some element of the experimental protocol disrupted this process.…”
Section: Discussionmentioning
confidence: 99%
“…During intense nociceptive input, glycine released from inhibitory interneurons can escape the synaptic cleft and reach adjacent NMDA receptors by spillover, hence facilitating excitatory neurotransmission. Suppression of this process can also induce analgesia (76). Therefore, it has been reported that manipulation of the synaptic glycine concentrations affects nociception by influencing both excitatory and inhibitory transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In structures where glycinergic innervation is abundant, such as in the retina and the spinal cord, glycine that serves as an endogenous co-agonist at NMDARs originates from glycinergic terminals [70,71]. In those preparations, it was demonstrated that glycine released at inhibitory synapses spills over and diffuses to bind to remote NMDARs.…”
Section: Co-agonist Control Of Extrasynaptic Nmdarsmentioning
confidence: 99%